The Impact of Sustainability Reports on the Financial Performance of Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2023 - A.F. Nst, Ledia; Deswita, Santi; Rusyaida, Rusyaida; Putra, Indika Juang (Yayasan Rahmat Islamiyah, 2025)
This study highlights the influence of sustainability reporting on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). A quantitative research method was employed, utilizing secondary data obtained from annual and sustainability reports. The sample was selected using purposive sampling, comprising 45 observations from nine companies over five years. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS version 24. The test results show that the calculated t-value (0.643) is lower than the t-table value (2.017), and the significance value (0.524) exceeds the 0.05 threshold. Therefore, it can be concluded that sustainability reporting does not have a significant effect on a company’s financial performance. This finding is presumed to occur due to the absence of strict regulations mandating high-quality sustainability reporting and the lack of tangible incentives for companies that prepare comprehensive sustainability reports.